Success of Geothermal Wells : A Global Study - International Finance Corporation (Washington, DC, 2014)
The core objective of this project was to develop a sufficiently large database to allow statistically significant conclusions to be drawn on the success rates of geothermal wells worldwide (expressed as the number of successful wells developed as a proportion of total wells drilled in any given field). This report determines and analyzes that overall success rate, as well as those factors that potentially affect success including geology, resource enthalpy, and well depth. It seeks to assess the extent of any improvements in well success rates, and how far the likelihood of success increases as a developer learns more about any specific resource. This report also analyzes the power capacity of geothermal wells drilled and the factors affecting such capacity. This report is targeted at those with an interest in the risks pertaining to geothermal wells, and the subsequent probability of success. The information contained is of interest to geothermal developers, and to financers engaged in the risk assessment of such projects. This report, and the database and analysis on which it is based, may be used by stakeholders in the geothermal industry investigating the range of success rates seen in geothermal projects around the world, and the factors that influence such variation.